Study of cervical cytology in pap smears in a tertiary care hospital of North Maharashtra - Agrawal, Sakshi; Agrawal, Sumedh; Gupta, Prashant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Cervical cancer is the fourth leading cause of death in females worldwide. In India cervical cancer is the leading cause of morbidity and mortality. Cancer of cervix is preventable, and can be diagnosed at the pre-malignant stage with adequate and repetitive cytological screening by Papanicolaou (Pap) smears. Aim of this study was to study the role of Pap smear in detecting premalignant and malignant lesions as well as non-neoplastic lesions of cervix. Methods: It is a retrospective study of 240 pap smears studied from January 2022 to June 2022 and received in pathology department of a tertiary care hospital of north Maharashtra. Samples are collected from women between 21 to 65 years presenting with some gynecological problems. Smears were reported as per the 2014 Bethesda system. Results: Out of 240 women, 216 were having normal cytology and 146 cases with inflammatory changes. 10 cases were unsatisfactory. 5 cases of ASCUS, 1 case of SCC, 2 cases of HSIL and 6 cases of LSIL were observed. Conclusions: Pap smear test is a simple, safe, noninvasive, economical OPD based procedure to detect pervasive cervical epithelial lesions. Every woman should undergo Pap test at least once in her life before the age of 45 years.